2017
DOI: 10.1016/j.envint.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and exposure to ambient air pollution in two prospective cohorts

Abstract: Long-term exposure to air pollution has been associated with several adverse health effects including cardiovascular, respiratory diseases and cancers. However, underlying molecular alterations remain to be further investigated. The aim of this study is to investigate the effects of long-term exposure to air pollutants on (a) average DNA methylation at functional regions and, (b) individual differentially methylated CpG sites. An assumption is that omic measurements, including the methylome, are more sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 59 publications
7
75
0
Order By: Relevance
“…Methylation may be another potential biologic mechanism as PAH sources have been associated with hypo‐ and hypermethylation at multiple promoter regions in breast tumors and in blood of control women . Two of the ESCAPE cohorts conducted a genome‐wide DNA methylation study in relation to exposure to gaseous and particulate matter pollutants and found an association between global hypomethylation with exposure to NO x ( p = 0.089) and NO 2 ( p = 0.014) but not to exposures of particulate matter . High epigenome‐wide DNA methylation in prediagnostic blood samples has been associated with lower risk of breast cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation may be another potential biologic mechanism as PAH sources have been associated with hypo‐ and hypermethylation at multiple promoter regions in breast tumors and in blood of control women . Two of the ESCAPE cohorts conducted a genome‐wide DNA methylation study in relation to exposure to gaseous and particulate matter pollutants and found an association between global hypomethylation with exposure to NO x ( p = 0.089) and NO 2 ( p = 0.014) but not to exposures of particulate matter . High epigenome‐wide DNA methylation in prediagnostic blood samples has been associated with lower risk of breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…35 Two of the ESCAPE cohorts conducted a genome-wide DNA methylation study in relation to exposure to gaseous and particulate matter pollutants and found an association between global hypomethylation with exposure to NO x (p = 0.089) and NO 2 (p = 0.014) but not to exposures of particulate matter. 47 High epigenome-wide DNA methylation in prediagnostic blood samples has been associated with lower risk of breast cancer. 48 Thus, it is a reasonable hypothesis that hypomethylation, often a hallmark of genetic instability, in relation to exposure to traffic-related air pollutants may lead to high risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…prenatal famine 60 ) as well as environmental conditions later in life (e.g. air pollution 61,62 ). Alterations in DNA methylation might hold great potential as surrogate markers for factors that are not easily measured by questionnaires-for instance, Boyne et al 62 and Johansson et al 63 have found that long-term hormonal exposure can be proxied through DNA methylation signatures.…”
Section: Timing Of Sample Collection For Dna Methylation Measurementmentioning
confidence: 99%
“…Genetic polymorphisms also interact with many other environmental stressors to generate asthma phenotypes such as decreased lung function, adult‐onset asthma, or the severe asthma phenotype . Air pollution also induces transcriptomic, epigenomic, and metabolomic responses …”
Section: Framing the Issuementioning
confidence: 99%